The role of vitamin D in pediatric systemic lupus erythematosus - a double pawn in the immune and microbial balance - Lupu, Vasile Valeriu; Lupu, Ancuta; Jechel, Elena; Starcea, Iuliana Magdalena; Stoleriu, Gabriela; Ioniuc, Ileana; Azoicai, Alice; Danielescu, Ciprian; Knieling, Anton; Borka-Balas, Reka; Salaru, Delia Lidia; Revenco, Ninel; et al. (Frontiers in Immunology, 2024)
Having increased popularity during the Covid-19 pandemic, vitamin D3 is currently impressing thanks to the numerous researches aimed at its interactions with the body’s homeostasis. At the same time, there is a peak in terms of recommendations for supplementation with it. Some of the studies focus on the link between autoimmune diseases and nutritional deficiencies, especially vitamin D3. Since the specialized literature aimed at children (patients between 0-18 years old) is far from equal to the informational diversity of the adult-centered branch, this review aims to bring up to date the relationship between the microbial and nutritional balance and the activity of pediatric systemic lupus erythematosus (pSLE). The desired practical purpose resides in a better understanding and an adequate, individualized management of the affected persons to reduce morbidity. The center of the summary is to establish the impact of hypovitaminosis D in the development and evolution of pediatric lupus erythematosus. We will address aspects related to the two entities of the impact played by vitamin D3 in the pathophysiological cascade of lupus, but also the risk of toxicity and its effects when the deficiency is over supplemented (hypervitaminosis D). We will debate the relationship of hypovitaminosis D with the modulation of immune function, the potentiation of inflammatory processes, the increase of oxidative stress, the perfusion of cognitive brain areas, the seasonal incidence of SLE and its severity. Finally, we review current knowledge, post-pandemic, regarding the hypovitaminosis D – pSLE relationship.